A multi-centre, prospective, randomised controlled feasibility study of plantar resistance exercise therapy for venous leg ulcers – Results of the PREVUE study. (May 2020) - Jonker, Leon; Todhunter, Jane; Schutter, Jose; Halliday, Charlotte; Fisher, Stacey
Objectives: To evaluate the feasibility of an interventional study involving a seated plantar resistance exercise programme, using a StepIt pedal, aimed at promotion of venous leg ulcer healing. Methods: Thirty-two venous leg ulcer patients, recruited from community, GP and hospital settings, were randomised to either a standard care or adjuvant StepIt exercise programme arm for up to 12 weeks. The exercise involved a twice daily routine of 10 times 1 min of exercise, i.e. 2 s push and 2 s lift repetitions (equating to 300 daily 'steps'). Results: Complete healing of the venous leg ulcers was observed in 10 out of 15 (67%; StepIt cohort) and 7 out of 17 (41%; control cohort), respectively (p-value 0.18, Fisher's exact test). Baseline differences between the two cohorts were longer wound chronicity, less venous leg ulcer-related pain and better venous leg ulcer-related quality of life in the StepIt cohort. One adverse event, involving increased wound exudate and slough production, was observed in a participant using StepIt, and no study withdrawals were recorded in either arm. StepIt users whose wound had completely healed by week 12 were more likely to be compliant with the exercise programme (self-reported) and more positive about the trial experience; however, all would recommend the device to others. Conclusions: Seated plantar resistance exercise shows promise and may accelerate venous leg ulcer wound healing. The StepIt pedal is well-received by patients, and its efficacy may depend on the degree of patient compliance with the exercise programme. Further larger scale studies are indicated to allow more concrete inferences to be made on the clinical and potential health economics impact that this device may have.